Seroepidemiological study of feline coronavirus (FCoV) infection in domiciled cats from Botucatu, São Paulo, Brazil - Almeida, Ariani C.S. [UNESP]; Galdino, Maicon V. [UNESP]; Araújo, João P. [UNESP] (FapUNIFESP (SciELO), 2019)
Feline coronavirus (FCoV) is responsible for causing one of the most important infectious diseases of domestic and wild felids, the feline infectious peritonitis (FIP), which is an immune-mediated, systemic, progressive and fatal disease. FCoV is highly contagious, and infection is common in domestic feline populations worldwide. The present study aimed to determine the seropositivity of FCoV infection and its associated epidemiological variables (risk factors) in domiciled cats in Botucatu, São Paulo, Brazil. Whole blood samples (0.5-1mL) were collected from 151 cats, and sera were extracted by centrifugation. These sera were tested by an commercial enzyme-linked immunosorbent assay (ELISA) for the detection of IgG anti-FCoV antibodies. The assessed risk factors were age range, breed, gender, reproductive status, outdoor access and rearing mode (living alone or in a group). The seropositivity was 64.2% (97/151). There was no statistical significance for risk factors related to breed, gender or rearing mode. There were significant differences in seropositivity (p-values ≤0.05) for age range (p=0.0157), reproductive status (p=0.0074) and outdoor access (p=0.0001). This study verified a wide dissemination of FCoV in the studied population, with a higher than expected seropositivity for indoor cats. Among the risk factors, age range, reproductive status and outdoor access presented statistically significant differences, thus helping to establish an epidemiological profile of this population.
Keywords: Brazil; Cats; Domiciled cats; FCoV; Feline coronavirus; Seroepidemiology; São Paulo; Viroses